Analysis of Factors Affecting Decline in Clinical Patient Visits at the Riau Provincial Health Office Laboratory - Rista, Indriana; Jespisah, Doni; Daniel, Sangap (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2026)
Background: The decline in clinical patient visits poses a strategic challenge in improving the quality of health laboratory services. Service data from the Health and Environmental Laboratory Technical Implementation Unit of the Riau Provincial Health Office indicates a 43.5% decline in clinical patient visits by 2024, despite an increase in environmental service visits. This study aims to analyze the factors influencing the decline in clinical patient visits. Method: The research used a qualitative approach through in-depth interviews, observation, and document review. Primary informants included the Head of the Clinical Services Section and Doctors, while supporting informants included Registration Officers and Clinical Patients. Data analysis was conducted using triangulation of sources, methods, and data to ensure the validity of the results. Result: The decline in clinical patient visits was influenced by a lack of promotion of laboratory services, low communication skills of frontline staff in providing excellent service, uncomfortable waiting rooms, limited digital service facilities, including the lack of an electronic medical record system, and weak referral networks with other healthcare facilities. Conclusion: Recommended improvement efforts include enhancing clinical service human resource competencies, optimizing service promotion, improving waiting room facilities, developing digital service systems, and strengthening referral networks to restore clinical patient visit numbers and increase community satisfaction with regional laboratory services.